Lack of variability in the mitochondrial DNA D-loop region in Kedah Kelantan cattle - Yow, Weng Kit; Panandam, Jothi Malar; Idris, Ismail; Mohd Saleh, Norihan (2009)
The Kedah Kelantan, which is a Bos indicus breed, is the indigenous cattle of Malaysia. Mitochondrial DNA displacement loop (D-loop) region is often used to analyze the phylogeny of closely related breeds within species. Variations that occur in this region can be used as genetic markers for mtDNA. The objective of this study was to evaluate the genetic variability in the mitochondrial D-loop region in the Kedah Kelantan cattle. DNA was extracted from the blood of 30 Kedah Kelantan cattle. The D-loop region was amplified using polymerase chain reaction (PCR) and the primers 5’ CCCAAAGCTGAAGTTCTATT 3’ (forward) and 5’ TTGGGTTAAGCTACATCAAC 3’ (reverse). The size of the amplified PCR product was 964 bp. The PCR product was then digested with six restriction endonucleases (RE): ApaI, BstXI, TaqI, BamHI, DdeI and HinfI. Three fragments were detected using Dde I and the rest of the RE produced two fragments each. No polymorphism was revealed for all six RE. The results indicated no variation in the D-loop region of the Kedah Kelantan cattle as far as these six RE were concerned.